Identification of novel TDRD7 isoforms - Skorokhod, O.M.; Gudkova, D.O.; Filonenko, V.V. (Вiopolymers and Cell, 2011)
Aim. The aim of our study was to investigate the tudor domain-containing protein 7 (TDRD7 ) subcellular
localization, which could be linked to diverse functions of this protein within the cell. Methods. In this study we
employed cell imaging technique for detecting TDRD7 subcellular localization, Western blot analysis of
HEK293 cell fractions with anti-TDRD7 monoclonal antibodies and bioinformatical search of possible TDRD7
isoforms in Uniprot, Ensemble, UCSC databases. Results. We have observed specific TDRD7-containing
structures in cytoplasm as well as in the nucleus in HEK293 cells. The Western blot analysis of subcellular
fractions (cytoplasm, mitochondria, nucleus) allowed us to detect three lower immunoreactive bands, with the
aproximate molecular weight of 130, 110 and 60 kDa (we termed them as TDRD7b, TDRD7g and TDRD7d) and
specific subcellular localization. The bioinformatical analysis of TDRD7 primary structure allowed us to
determine two alternative transcripts from TDRD7 gene coding for proteins with calculated molecular weight of
130 and 60 kDa. Conclusion. The presented data demonstrate the existence at protein level of potential TDRD7
isoforms: TDRD7b, TDRD7g and TDRD7d. The expression profile of these splice variants and their role in cells
remains to be elucidated.
Keywords: TDRD7, S6 kinase, isoform, piRNAs, translation. Мета. Мета досліджень полягала у вивченні внутрішньоклітинної локалізації TDRD7, що може бути пов’язано з різними функціями даного білка в клітинах. Методи. Застосовано метод імуноцитохімії для детекції субклітинної локалізації TDRD7, вестерн-блот аналіз клітинних фракцій НЕК293 з використанням
анти-TDRD7 моноклональних антитіл та біоінформатичний пошук можливих ізоформ TDRD7 у базах даних Uniprot, Ensemble,
UCSC. Результати. Специфічні TDRD7-вмісні структури виявлено в цитоплазмі, а також у ядрах клітин НЕК293. Імуноблотаналізом субклітинних фракцій (цитоплазма, мітохондрії, ядро)
детектовано три імунореактивні смуги з молекулярними масами
130, 110 і 60 кДа (ми назвали їх TDRD7b, TDRD7g і TDRD7d), які до
сьогодні не були охарактеризовані. Біоінформатичним аналізом
первинної структури TDRD7 визначено два альтернативних
транскрипти TDRD7-гена, продукти трансляції яких відповідають двом гіпотетичним ізоформам, ідентифікованим в імуноблоті (TDRD7b (130 кДа) та TDRD7d (60 кДа)). Висновки. Отримані дані вказують на можливість існування потенційних ізоформ TDRD7: TDRD7b, TDRD7g і TDRD7d у клітинах НЕК293 на
білковому рівні. З’ясування особливостей експресії та ролі нових
форм TDRD7 у клітинах потребує подальших досліджень.
Ключові слова: TDRD7, S6 кіназа, ізоформа, піРНК, трансляція. Цель. Цель исследования состояла в изучении внутриклеточной
локализации TDRD7, что может быть связано с различными
функциями данного белка в клетках. Методы. Применен метод
иммуноцитохимии для детекции субклеточной локализации
TDRD7, вестерн-блот анализ клеточных фракций НЕК293 с использовавнием анти-TDRD7 моноклональных антител и биоин -
форматический поиск возможных изоформ TDRD7 в базах данных Uniprot, Ensemble, UCSC. Результаты. Специфические
TDRD7-содержащие структуры выявлены в цитоплазме, а также в ядрах клеток НЕК293. Иммуноблот-анализом субклеточных фракций (цитоплазма, митохондрии, ядро) определены три
иммунореактивные полосы с молекулярными массами 130, 110 и
60 кДа (мы назвали их TDRD7b, TDRD7g и TDRD7d), которые до
настоящего времени не были охарактеризованы. Биоинформатическим анализом первичной структуры TDRD7 детектированы два альтернативных транскрипта TDRD7-гена, продукты
трансляции которых соответствуют двум гипотетическим
изоформам, идентифицированным в иммуноблоте (TDRD7b (130
кДа) и TDRD7d (60 кДа)). Выводы. Полученные данные указывают на возможность существования потенциальных изоформ
TDRD7: TDRD7b, TDRD7g и TDRD7d в клетках НЕК293 на белковом уровне. Выяснение особенностей экспрессии и роли новых
форм TDRD7 в клетках требует дальнейших исследований.
Ключевые слова: TDRD7, S6 киназа, изоформа, пиРНК,
трансляция.